The bimodal initial mass function in the Orion nebula cloud. Issue 2 (12th May 2016) - Drass, H.; Haas, M.; Chini, R.; Bayo, A.; Hackstein, M.; Hoffmeister, V.; Godoy, N.; Vogt, N.
Abstract: Due to its youth, proximity and richness, the Orion nebula cloud (ONC) is an ideal testbed to obtain a comprehensive view on the initial mass function (IMF) down to the planetary mass regime. Using the HAWK-I camera at the VLT, we have obtained an unprecedented deep and wide near-infrared JHK mosaic of the ONC (90 per cent completeness at K ∼ 19.0 mag, 22 × 28 arcmin 2 ). Applying the most recent isochrones and accounting for the contamination of background stars and galaxies, we find that ONC's IMF is bimodal with distinct peaks at about 0.25 and 0.025 M⊙ separated by a pronounced dip at the hydrogen burning limit (0.08 M⊙ ), with a depth of about a factor of 2–3 below the log-normal distribution. Apart from ∼920 low-mass stars ( M < 1.4 M⊙ ) the IMF contains ∼760 brown dwarf candidates and ∼160 isolated planetary mass object candidates with M > 0.005 M⊙, hence about 10 times more substellar candidates than known before. The substellar IMF peak at 0.025 M⊙ could be caused by brown dwarfs and isolated planetary mass objects which have been ejected from multiple systems during the early star formation process or from circumstellar discs.